(untitled) (International Journal of Engineering and Computer Science, 2014)
Online recruitment provides a number of benefits such as reducing advertising cost, unlimited access to job adverts, sophisticated management tools and easier interaction between advertiser and jobseekers. But with every system that has merits, it also has its demerits. The demerit for this system is majorly that, the system does not distinguish between qualified and unqualified job applications sent to the advertiser which clusters the advertisers profile or mail depending on where the application is to be received. The aim of this study is to ensure that the system contains a filtration tool which is an online test that contains questions from the graduate management admission test, in other to distinguish the qualified from the unqualified applications and determine the eligibility of the jobseeker for that position and to provide a common profile for jobseekers such as a basic curriculum vitae CV to make the short listing process easier for the advertisers rather than looking through thousands of CVs with different format. The work included the design of an online job recruitment portal, where PHP, HTML, Java Script, CSS and MySQL are the programming language used to develop the system. Hence, the system is a web based application that links job seekers to job adverts of their choice and allows them to apply for the position(s). Therefore if the test is passed, job seekers application will be sent to the advertiser for short listing and the advertiser then picks the preferred candidate for the position.